Pengaruh kualitas informasi website yellow fit kitchen terhadap kepuasan visitor (Jurnal Kajian Media, 2022)
Nowadays, various industries in Indonesia have applied information technology, namely the internet to support their business activities. The industry that applies information technology in its activities is the food industry, especially this industry will always be operate because food and beverages are basic human needs. Yellow Fit Kitchen as one of the food and beverages industries from Indonesia uses website as a medium in distributing information from companies to the public. The factor that will be examined in this study is the quality of information from the Yellow Fit Kitchen website on the satisfaction of website visitors. Through a survey method using a questionnaire distributed to 50 respondents, it was found that there is an influence of the quality of information on the Yellow Fit Kitchen website on the satisfaction of visitors to the Yellow Fit Kitchen website, as seen from the calculated T value of 46,302 which is greater than T table 1,677. Through the output of R2, it was found that 97.8% of the variation in visitor satisfaction was caused by variations in the quality of information, while the remaining 0.1% was explained by other factors outside of this study. Keywords: Information Quality, Customer Catisfication, Internet.